Effect of inorganic and organic zinc supplementation on semen quality in Murrah buffalo (Bubalus bubalis) bulls - IMAM, S; ANSARI, M R; Kumar, RIPU SUDAN; MUDGAL, VISHAL; VARSHEN, V P; DAS, R S (The Indian Journal of Animal Reproduction, 2023)
The present study-was conducted to elucidate the effect of inorganic (zinc sulphate) and organic(zinc propionate)' zinc supplementation on in vitro semen fertility and semen quality in buffalo bulls. Twelvebuffalo bulls of about 2 years of age and 302.0± 1.6 kg average body weight were divided into 3 equalgroups. All the animals were fed on wheat straw and concentrate mixture to meet their nutrient requirement;I_ Animals in-group I were treate·d as control, whereas animals in group II and III were experimental andwere supplemented ·with 70 ppm and 3 5 ppm zinc through zinc sulphate and zinc propionate, respectivel1i1· This feeding practice lasted for 6 months. Bulls were trained to donate semen into artificial vagina. After3 months of experimental feeding, 6 ejaculates from each bull were collected to study the effect of zincsupplementation (?D sperm fertility and semen characteristics. Statistical analysis of the data revealed thatthete was no effect of zinc supplementation on semen pH and semen volume; however, sperm concentration. mass motility and individual motility differed significantly (P
Keywords: Buffalo bull, Semen; Zinc sulphate; Zinc propionate; Semen characteristics